Projected Cooling and pco2 Conditions in Upwelling Zones and Their Influence on a Prominent Rocky Shore Ecosystem Engineer - Garcia-Herrera, C (Academic Press, 2025)
By the end of the century, upwelling zones are expected to undergo distinct changes due to the accumulation of greenhouse gases in the atmosphere. These changes include an intensification of the winds causing upwelling, further reducing sea surface temperatures (cooling), and an intensification of ocean acidification (OA). While only a few studies have evaluated the influence of cooling conditions in these systems, even fewer have assessed the combined effects of cooling and projected OA. This study addressed this gap by exposing juveniles of the intertidal purple mussel (Perumytilus purpuratus), a prominent intertidal ecosystem engineer, to distinct temperatures and pCO2 levels. Using a mesocosm system and a 2 x 2 factorial design, groups of purple mussels were exposed to current (15 degrees C) and projected cooling conditions (10 degrees C), and current and projected pCO2 levels (500 and 1500 mu atm, respectively). After two months, we quantified mussel growth, calcification, byssus thread production, clearance, and metabolic rates. Growth, calcification, and byssus thread production rates were consistently affected by temperature and by the interaction between temperature and pCO2: At current temperatures (15 degrees C) all these variables increased in response to OA, but when exposed to projected cooling conditions (10 degrees C), these trends reversed and declined with OA. Mussel clearance rates followed the same trend, but in this case the only significant factor was the interaction between variables. Meanwhile, metabolic rates declined with temperature. A close examination of the variation among treatments suggests that the main changes were consistently associated with a sharp decline in most response variables to a combination of cooling and highpCO2 conditions. Hence, projected end of the century cooling and OA are likely to have direct (negative) effects on this habitat-forming species. Indirectly, the combination of these stressors may weaken mussel bed structure and reduce habitat complexity, thereby halting the benefits provided to associated intertidal communities.